Picrasidine G decreases viability of MDA-MB 468 EGFR-overexpressing triple-negative breast cancer cells through inhibition of EGFR/STAT3 signaling pathway - Yamashita, Naoya; Kondo, Manami; Zhao, Shuai; Li, Wei; Koike, Kazuo; Nemoto, Kiyomitsu; Kanno, Yuichiro (Bioorganic & Medicinal Chemistry Letters, 2017)
[Display omitted] •Picrasidine G decreased viability of EGFR-overexpressing triple-negative breast cancer cells.•Picrasidine G increased caspase-dependent apoptotic cells.•Picrasidine G inhibited EGF-induced STAT3 phosphorylation. Targeted therapy is unavailable for treating patients with triple-negative breast cancer (TNBC), which accounts for approximately 15% of all breast cancers. Overexpression of epidermal growth factor receptor (EGFR) is observed in approximately 30–60% of TNBCs. Therefore, developing novel strategies for inhibiting EGFR signaling is required. In the present study, a natural compound library was screened to identify molecules that target TNBCs that overexpress EGFR. Picrasidine G (PG), a naturally occurring dimeric alkaloid produced by Picrasma quassioides, decreased the viability of the MDA-MB 468 cell line (TNBCEGFR+) compared with other breast cancer cell lines. PG treatment increased markers of apoptosis, including chromatin condensation, sub-G1 population, cleavage of caspase 3 and cleavage of poly (ADP-ribose) polymerase (PARP). PG inhibited the phosphorylation of signal transducer and activator of transcription 3 (STAT3) and inhibited transcription of the STAT3-target gene encoding survivin. Further, PG inhibited EGF-induced STAT3 phosphorylation but not interleukin-6 (IL-6)-induced STAT3 phosphorylation. These results suggest that PG may contribute to the development of targeted therapy of patients with EGFR-overexpressing TNBC.